(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The article begins by elucidating the significance of nutrition in sports, emphasizing its influence on energy levels, endurance, recovery, and overall health. It explores the diverse diets commonly adopted by athletes, including macronutrient ratios, micronutrient considerations, and specialized dietary approaches tailored to different sports. Furthermore, the article delves into the complex factors that influence diet selection among athletes. It discusses the interplay of individual requirements, training intensity, dietary restrictions, and cultural influences, offering insights into the decision-making process athletes face when crafting their nutrition plans.